Sistem Kendali Dan Monitoring Beban-Beban Listrik Rumah Berbasis Processing Line Comunication ( PLC ) - Teguh Yuwono (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2015)
The use of electrical loads in the residence would be more effective and efficient if there is an automation control systems, and monitoring the set, resulting in electricity savings in all electrical and electronic equipment which affect the cost of electricity payment every month as well lifespan becomes longer. In this paper applied a method of design and manufacture of hardware systems (hadware) and software (software) by utilizing the Technology Power Line Communication (PLC). The design unit PLC based products. The design of the economic value of the product of the energy cost savings each month. Product Series P3oT PLC unit which serves as the control and monitoring of electrical loads PLC-based residential affecting the electricity cost savings of up to 37% every month. The value of benefits Benefit Cost Ratio (BCR) of 1.1 or (BCR> 1).